1997
DOI: 10.1177/000331979704801101
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Improvement After AV Nodal Ablation and Pacemaker Implantation for Refractory Atrial Fibrillation and Atrial Flutter

Abstract: Symptomatic Improvement was evaluated in 64 patients with drug-refractory atrial fibrillation or atrial flutter who underwent atrioventricular (AV) nodal ablation and permanent pacemaker implantation. The arrhythmias were chronic in 40 patients and paroxysmal in 24 patients. All were refractory to multiple drugs (3.7 +/- 1.5) and had severe symptoms: palpitations (58 patients), dyspnea (n=58), dizziness (n=38), asthenia (n=37), and chest pain (n=20). All underwent AV nodal ablation and single- (n=39) or dual-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…For patients with intractable atrial fibrillation, AV nodal ablation has been recommended as an alternative treatment option 25 . Concomitant pacemaker implantation improves cardiac performance, exercise tolerance, and quality of life in adult patients with atrial flutter or atrial fibrillation 26,38,39 . Likewise, we noted a significantly improved clinical status of our patients, although 2 patients were still in IART or atrial ectopic tachycardia.…”
Section: Discussionsupporting
confidence: 53%
“…For patients with intractable atrial fibrillation, AV nodal ablation has been recommended as an alternative treatment option 25 . Concomitant pacemaker implantation improves cardiac performance, exercise tolerance, and quality of life in adult patients with atrial flutter or atrial fibrillation 26,38,39 . Likewise, we noted a significantly improved clinical status of our patients, although 2 patients were still in IART or atrial ectopic tachycardia.…”
Section: Discussionsupporting
confidence: 53%
“…Although those symptoms that result from a fast and irregular ventricular rate may show dramatic improvement, the symptoms that occur from the loss of atrial contraction and AV synchrony are unlikely to improve. This procedure leads to rate control but not rhythm control, hence, the atria will keep on fibrillating, and the ventricular response will dependent on the implanted permanent pacemaker [34][35][36][37][38][39] .…”
Section: Atrioventricular Nodal Catheter Ablationmentioning
confidence: 99%
“…In general, several retrospective studies, randomized control studies, and meta-analysis reported beneficial evidence that AVN catheter ablation followed by permanent pacemaker implantation are a valuable palliative therapy for highly symptomatic, drug-refractory AF patients. Many retrospective studies have documented significant acute and long-term improvement in left ventricular function, symptoms, cardiac performance, exercise tolerance, clinical outcomes, and quality of life in selected patients with paroxysmal and persistent drug-refractory AF who have undergone AVN ablation and permanent pacemaker implantation [30][31][32][33][34][35][36][37] .…”
Section: Clinical Outcomes In Avn Ablation Studiesmentioning
confidence: 99%
“…If pharmacological treatment is unsuccessful in optimizing ventricular rate response, radiofrequency (RF) ablation of the atrioventricular (AV) junction and induction of complete AV block with subsequent implantation of a pacemaker is an effective therapeutic alternative. [9][10][11] The most significant drawback of this therapeutic approach is a lifelong pacemaker dependency. In addition, in a minority of patients, AVN ablation can lead to hemodynamic deterioration together with progression of mitral regurgitation.…”
Section: Introductionmentioning
confidence: 99%